Plasma Lipocalin 2 in Alzheimer's disease: potential utility in the differential diagnosis and relationship with other biomarkers - Hermann, Peter (2022)
Background: Lipocalin-2 is a glycoprotein that is involved in various physiological and pathophysiological processes. In the brain, it is expressed in response to vascular and other brain injury, as well as in Alzheimer’s disease in reactive microglia and astrocytes. Plasma Lipocalin-2 has been proposed as a biomarker for Alzheimer’s disease but available data is scarce and inconsistent. Thus, we evaluated plasma Lipocalin-2 in the context of Alzheimer’s disease, differential diagnoses, other biomarkers, and clinical data. Methods: For this two-center case-control study, we analyzed Lipocalin-2 concentrations in plasma samples from a cohort of n = 407 individuals. The diagnostic groups comprised Alzheimer’s disease (n = 74), vascular dementia (n = 28), other important differential diagnoses (n = 221), and healthy controls (n = 84). Main results were validated in an independent cohort with patients with Alzheimer’s disease (n = 19), mild cognitive impairment (n = 27), and healthy individuals (n = 28). Results: Plasma Lipocalin-2 was significantly lower in Alzheimer’s disease compared to healthy controls (p < 0.001) and all other groups (p < 0.01) except for mixed dementia (vascular and Alzheimer’s pathologic changes). Areas under the curve from receiver operation characteristics for the discrimination of Alzheimer’s disease and healthy controls were 0.783 (95%CI: 0.712–0.855) in the study cohort and 0.766 (95%CI: 0.627–0.905) in the validation cohort. The area under the curve for Alzheimer’s disease versus vascular dementia was 0.778 (95%CI: 0.667–0.890) in the study cohort. In Alzheimer’s disease patients, plasma Lipocalin2 did not show significant correlation with cerebrospinal fluid biomarkers of neurodegeneration and AD-related pathology (total-tau, phosphorylated tau protein, and beta-amyloid 1-42), cognitive status (Mini Mental Status Examination scores), APOE genotype, or presence of white matter hyperintensities. Interestingly, Lipocalin 2 was lower in patients with rapid disease course compared to patients with nonrapidly progressive Alzheimer’s disease (p = 0.013). Conclusions: Plasma Lipocalin-2 has potential as a diagnostic biomarker for Alzheimer’s disease and seems to be independent from currently employed biomarkers.